2014
DOI: 10.1038/sc.2014.42
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of whole-body computed tomography in spinal cord-injured patients with sepsis

Abstract: Although in the majority of cases, the findings were non-specific, a small number of patients had significant pathology identified by CT, which influenced their management significantly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Examples of such a scenario may include patients with septic shock or fever with altered mental status but no clear source of infection after initial evaluation with a history, physical examination, laboratory work, and chest radiography. 32 , 33 , 34 …”
Section: Discussionmentioning
confidence: 99%
“…Examples of such a scenario may include patients with septic shock or fever with altered mental status but no clear source of infection after initial evaluation with a history, physical examination, laboratory work, and chest radiography. 32 , 33 , 34 …”
Section: Discussionmentioning
confidence: 99%
“…In a study of SCI patients ( n = 22) with suspected or known sepsis, investigators found that chest-abdomen-pelvis CT identified a specific radiologic diagnosis in 14 % and non-specific findings in 68 %. Although the bulk of findings were non-specific, a small portion of patients had significant radiologic findings that influenced their management [ 54 ].…”
Section: Discussionmentioning
confidence: 99%